Hollywood Be Thy Name African American Religion in American Film, 1929-1949. - Weisenfeld, Judith (CA : University of California Press, 2007)
From the earliest years of sound film in America, Hollywood studios and independent producers of "race films" for black audiences created stories featuring African American religious practices. In the first book to examine how the movies constructed images of African American religion, Judith Weisenfeld explores these cinematic representations and how they reflected and contributed to complicated discourses about race, the social and moral requirements of American citizenship, and the very nature of American identity. Drawing on such textual sources as studio production files, censorship recor
List of Illustrations; Acknowledgments; Introduction; 1. "'Taint What You Was, It's What You IsToday"; 2. "'De Lawd' a Natchel Man"; 3. "A Mighty Epic of Modern Morals"; 4. "Saturday Sinners and Sunday Saints"; 5. "A Long, Long Way"; 6. "Why Didn't They Tell Me I'ma Negro?"; Conclusion; Filmography; Notes; Select Bibliography; Index
Description based upon print version of record.
Keywords: African Americans in motion pictures; Motion pictures -- United States; Religion in motion pictures; African Americans in motion pictures; Religion in motion pictures; Motion pictures -- United States; ART / Film & Video; PERFORMING ARTS / Film & Video / Reference; Electronic books